Impact on the trade negotiations between the European Union and two African Regional Economic Communities - CGIAR Research Program on Policies, Institutions, and Markets (2017)
The trade relations between African countries and the European Union have high stakes for both regions. The negotiations of the Economic Partnership Agreements have remained a sensitive agenda since 2007. PIM modelling capacity has provided independent quantifications of the agreements. The research outputs have been at the core of the official impact assessment to the policy makers. The current policy outcomes are consistent with the results provided and contrast the outcomes of trade agreements on development and food security.